FAKTOR-FAKTOR KETEPATAN WAKTU PELAPORAN KEUANGAN (Students' Journal of Accounting and Banking, 2012)
This study aims to examine the debt to equty ratio, profitability, auditor quality, firm size and firm age on timeliness of corporate financial reporting and the Real Estate Property. All companies listed on the Indonesia Stock Exchange in the compulsory annual financial report. Timeliness of reporting financial information is required by the users of financial statements such as accountants, managers, financial analysts, and investors. Financial statements are the elements that are essential in making investment decisions. Study sample was 56 companies Real Estate and Property listed on the Stock Exchange in 2009-2010. Sampling technique using a purposive sampling method. The analysis used in this study using Logistic Regression is used as dummy variables. Test Model Hosmer and Lemeshow including Goodness of Fit Test's, Log Likelihood and Naglekerke R Square. Based on the statistical t test results indicate the age of the company are significant positive impact on timeliness, whereas no significant positive effect DER, ROA is significantly negative effect, the quality auditor is significant and positive effect of firm size is not significant positive effect on the timeliness of financial reporting.Keywords: Timeliness, Debt to Equity Ratio, Profitability, Company Size, Company Age, Quality Auditor.